Conformational ensembles of the magnesium channel CorA reveal structural basis for channel gating - Satchal K. Erramilli; Kamil Nosol; Krzysztof Pietrzak-Lichwa; Nicolaus Schmandt; Tian Li; Piotr Tokarz; Jingkai Hou; Minglei Zhao; Eduardo Perozo; Anthony A. Kossiakoff (Proceedings of the National Academy of Sciences, 2026)
In prokaryotes, CorA is the primary influx pathway for magnesium, a critical divalent cation in cellular physiology and biochemistry. Mechanistic studies show that homopentameric CorA is regulated through an intracellular [Mg 2+ ]-dependent negative feedback loop, involving the asymmetric participation of individual subunits. To understand the connection between asymmetry and activation, we used single-particle cryo-EM to solve sixteen structures of nanodisc-reconstituted CorA. We utilized conformation-specific synthetic antibodies to stabilize subtle but significant conformational differences in the cryo-EM structures. Our results demonstrate that CorA exists as a set of conformational ensembles, where population size inversely correlates with intracellular Mg 2+ concentration. These ensembles include channels with a variety of pore conformations, both constricted and dilated, suggesting a spectrum of active CorA functional states. The ensembles connect asymmetric structural transitions in the cytoplasmic domain with conformational changes in the permeation pathway via an electrostatic network, ultimately controlling channel-gating events. We believe that these results establish a framework for understanding magnesium homeostasis in prokaryotic systems.